Medición de usabilidad de un aplicativo móvil de aprendizaje de estudiantes de primaria en idioma huitoto murui bue en la comunidad Centro Arenal - Poclin Calampa, Juan Carlos (2022)
This research work is intended to develop and measure the usability of a mobile learning application for primary school students in Huitoto Murui Bue in the Centro Arenal community. The investigation is of an application type, with the solution design. The sample was represented by 10 users. The collection of information about the usability was based on the its questionnaire (System Usability Scale), which is a reliable and fast tool to measure the usability, the same that is made up of 10 questions, which are valued with a Likert scale 5 points. The most important results are: The efficacy of the usability of the mobile application of primary school students in Huitoto Murui Bue in the Central Arenal community is 100% and its effective 94.13 %. Consequently, the general research hypothesis is accepted: "If we measure the usability of a mobile learning application for primary school students in Huitoto Murui Bue, then satisfactory levels of usability greater than 90% can be determined."